HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE DAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS KARANGANYAR KOTA TASIKMALAYA - Natasha, Frieska Aulia; Maywati, Sri; Neni, Neni (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2025)
Chronic malnutrition during a child's growth and development is known as stunting. An unclean environment can cause a number of diseases, including diarrhea, which affects the body's ability to absorb nutrients and increases the risk of stunting. The purpose of this study was to determine the relationship between the incidence of stunting in toddlers and environmental sanitation in the working area of the Karanganyar Health Center, Taksikmalaya City. This study used a case-control design and was observational and analytical, the case population is toddlers who experience Stunting at the Karanganyar Health Center totaling 85 toddlers, the control population is toddlers who do not experience Stunting at the Karanganyar Health Center totaling 85 toddlers who compare case and control samples 1: 1, so that the total sample is 170 respondents. The sampling technique uses purposive sampling. Data analysis in this study uses Chi-Square. The results of the study showed that there was a significant relationship between clean water facilities (p = 0.000), waste management facilities (p = 0.001), healthy toilet facilities (p = 0.000), and wastewater disposal facilities (p = 0.010) with a history of diarrhea. There was a relationship between clean water facilities (p = 0.004), waste management facilitiesi (p = 0.000), healthy toilet facilitiesi (p = 0.003), waste water disposal facilitiesi (p = 0.000) and a history of diarrhea (p = 0.002) with the incidence of stunting. Based on the research results, it is recommended that the community pay more attention to clean water facilities, waste management facilities, toilet facilities and waste water disposal facilities in accordance with health requiremnets.